An Empirical study of Loan loss provisioning hypotheses for Chinese banking industry - Yuan, Yuchang (2017)
This paper provides an empirical study on the loan loss provisions (LLP) of 188 unconsolidated commercial banks in China from the year of 2007 to 2016. The loan loss provisioning in China is under multiple regulatory forces and the regime causes challengers for practical applications. Critical reforms have been made to the LLP regulatory regimes over the past few years. But contradictions arise from these regulatory standards. For the empirical research, a Cost-efficiency analysis is first carry out to estimate the efficiency scores in Chinese Banking industry over the last ten years. The Chinese banking industry was found to be cost efficient, the efficiency scores are then used as a potential explanatory variable for LLP behaviour model. The main estimations are the three LLP behaviour hypotheses regarding business cyclical provisioning, income smoothing and capital management. A joint model using two steps system Generalized Method of Moments (GMM) offers empirical implication for further analysis. While the income smoothing hypothesis are supported by empirical evidence, the cyclical provisions and capital management do not show significant practices in China. In the end, this paper also provided some practical limitation and improvement suggestions for the Loan loss provisioning analysis in China. KEYWORDS: Loan loss provisioning, Chinese Banking, Capital management hypothesis, Income smoothing, Cost-efficiency